Community-Based Tourism In Improving Community Welfare In Wanagiri Village, Sukasada District, Buleleng Regency - I Gede Putra NUGRAHA; Rahutama ATIDIRA; Made Dian Putri AGUSTINA (Journal of Tourism Economics and Policy, 2022)
This study aims to determine the effect of community participation on the welfare of the community through the quality of the destination. In this study, the population to be studied is the people who are directly involved in tourism activities and have an economic relationship with tourism activities in Wanagiri Village. The analytical technique used in this research is path analysis. The results of this study found that community participation had a positive but not significant effect on community welfare in Wanagiri Village, community participation had a positive and significant effect on destination quality in Wanagiri Village, destination quality had a positive and significant effect on community welfare in Wanagiri Village, community participation had an indirect effect. directly to the welfare of the community through the quality of consumer destinations in Wanagiri Village, community participation has an indirect effect on the welfare of the community through the quality of consumer destinations in Wanagiri Village.